2015
DOI: 10.3748/wjg.v21.i3.926
|View full text |Cite
|
Sign up to set email alerts
|

Deficient DNA mismatch repair is associated with favorable prognosis in Thai patients with sporadic colorectal cancer

Abstract: The prevalence of dMMR and BRAF V600E in Thai sporadic CRC patients was 15% and 11%, respectively. The dMMR phenotype was associated with a favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
2
15
0
1
Order By: Relevance
“…The distribution of primary site of MMR-D cancers enrolled in the study is rather similar to our cohort in which colorectal and gastric cancers showed high prevalence of MSI-H. The overall prevalence of MSI-H CRCs in our patients (11%, n=118) is slightly lower than that (15%, n= 211) reported in Thai population by Korphaisarn et al 11 Varied study populations and sample size may have resulted in the differences. While the previous Thai series included all stages of CRCs, all of our patients are presumably advanced stage and MSI testing was likely requested for immunotherapy.…”
Section: Discussionsupporting
confidence: 78%
“…The distribution of primary site of MMR-D cancers enrolled in the study is rather similar to our cohort in which colorectal and gastric cancers showed high prevalence of MSI-H. The overall prevalence of MSI-H CRCs in our patients (11%, n=118) is slightly lower than that (15%, n= 211) reported in Thai population by Korphaisarn et al 11 Varied study populations and sample size may have resulted in the differences. While the previous Thai series included all stages of CRCs, all of our patients are presumably advanced stage and MSI testing was likely requested for immunotherapy.…”
Section: Discussionsupporting
confidence: 78%
“…An additional 65 studies contained relevant data for KRAS, NRAS, or BRAF mutation status and tumor sidedness but did not report data specific to the mCRC population or data for mutation status by tumor sidedness. We contacted the authors of these studies for data availability and received relevant data from five studies . A total of 44 studies were therefore included in the narrative review and meta‐analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor phenotypes may vary with process of tumor infiltration and metastasis[30, 31]. For instance, mismatch repair deficiency (MMR) was associated with early-stage, non-metastatic CRC[32]. Also, expression of MHC-I has been found to decrease with tumor growth and invasion in CRC, with corresponding decreases in survival[33].…”
Section: Discussionmentioning
confidence: 99%